Error Analysis in Numerical Techniques using Euler's Method with a Practical Application (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
This paper focuses on error analysis and practical applications in modeling dynamic systems using Euler's method in numerical techniques. The dynamics of an infectious disease using the SIR (Susceptible-Infectious-Recovered) model were the primary objective of this paper which is simulated by Euler's method. By using the MATLAB code of Euler's method, the study investigates numerically how different parameters influence the spread of the disease over time, such as transmission and recovery rates, Moreover, the results illustrate Euler's method advantage in approximating solutions to ODEs, Finally, this study insight into the dynamics of disease spread and the potential for using numerical methods to optimize epidemic control strategies.